Socialization of Small Medium Enterprise (SME) Financial Management Accountability Based On Sharia Enterprise Theory In Kampung Moten Seremban Negeri Sembilan, Malaysia - Lince Bulutoding; Nur Rahmah Sari; Raodatul Jannah; Della Fadhilatunisa; Namla Elfa Syariati; Suhartono Suhartono (International Journal Of Community Service, 2024)
The aim of this International Community Service program is to socialize SMEs management based on Sharia Enterprise Theory (SET) in managing banking products as an additional fund for them. Moreover, this program was also carried out to socialize sharia-based business management, regarding SET concept-based accountability. This article is written to present the results of the FGD that illustrate that SMEs actors do not fully understand a SET concept-based accountability in managing their business. Accountability is still understood only as making financial reports in order to obtain credit. In understanding a SET concept-based accountability, SMEs actors must have an Islamic economics thinking paradigm that everything in this world belongs to Allah SWT and humans are only recipients of trust. Furthermore, based on the SET concept, there are three stakeholders in the Company that need to be met in accountability’s indicators, namely God, humans and the universe. Accountability applied by SMEs actors does not yet fully understand that the business they own is a mandate from Allah SWT which must always be accounted for, such as accurate financial reports are made so that Allah's rights are not oppressed, for example in the form of zakat.